Use Of The SAS Method To Improve Initial Writing Skills In Grade 1B Students Of Danukusuman Public Elementary School, Serengan Lota District, Surakarta For The 2021/2022 Academic Year - Khayati, Ari Nur (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study was to determine the increase in initial writing skills using the SAS method. This research was conducted because there were still many students who could not write letters, words and sentences correctly. This type of research is Classroom Action Research (CAR), the steps taken are (1) planning; (2) implementation; (3) observation; and (4) reflection and carried out in 2 learning cycles. The population in this study were class IB students at SDN Danukusuman Surakarta. Based on the research results, it was found that the results of tests carried out starting before the pre-cycle until the implementation of cycle 2. The average score obtained before the pre-cycle was 59.79 or only 41.67% of students achieved completeness KKM, increasing to 74.58 with the percentage of students who have achieved KKM to 66.67% in the first cycle and in the second cycle increased again to 88.96 or an increase of 87.05% compared to the pre-cycle. Thus it can be concluded that learning using the SAS method can improve students' ability to write beginning in grade 1 SDN Danukusuman.